Strategies for Implementing Telemedicine to Improve the Quality of Healthcare Services: A Literature Review - Paser, Yohanes Baptistuta; Hilal, Mukhammad; Inzaghi, Dimaz Rafly (Journal Research of Social Science, Economics, and Management, 2026)
Telemedicine, the use of communication technology to provide remote health services, has emerged as a transformative innovation in modern healthcare. This study aims to analyze the impact of telemedicine on healthcare service quality and identify strategies for its effective implementation. A literature review method was employed, sourcing articles from Google Scholar, PubMed, and ScienceDirect databases using keywords including "telemedicine," "telehealth," "quality of healthcare services," and "patient satisfaction." Inclusion criteria were articles published in the last 5-10 years, full-text availability, relevance to telemedicine and service quality, and publication in Indonesian or English. Exclusion criteria included opinion/editorial articles, irrelevant content, and duplicate publications. Ten articles meeting all criteria were analyzed using qualitative descriptive analysis. The findings demonstrate that telemedicine improves service access, reduces costs and waiting times, and achieves patient satisfaction levels comparable to face-to-face services. Telemedicine effectively supports diagnostic and patient follow-up processes. However, implementation faces significant obstacles including limited infrastructure (internet and electricity), regulatory and legal barriers, data security concerns, low digital literacy, and technology access inequality. This study concludes that telemedicine is an effective solution for improving healthcare quality and access, but successful implementation requires comprehensive strategies addressing infrastructure, regulatory frameworks, and digital literacy enhancement. The practical implications suggest that healthcare policymakers should prioritize telemedicine integration while systematically addressing existing barriers.